Mathematics with love the courtship correspondence of Barnes Wallis, inventor of the bouncing bomb - Stopes-Roe Mary (Hampshire Macmillan, 2005)
Mathematics with Love presents, for the first time, the result of this curious diktat: a series of witty, tender and totally accessible introductions to calculus, trigonometry and electrostatic induction that remarkably, wooed and won the girl. Deftly na
Keywords: Barnes Wallis; Correspondences; Mathematics